Implicit beliefs of disability and elite sport: the para-athlete experience - de Cruz, N. P.; Spray, C. M.; Smith, B. (Qualitative Research in Sport, Exercise and Health, 2019)
The purpose of this study was to explore the implicit beliefs and underlying motivational processes of para-athletes, and how these beliefs influenced perceptions of sport performance, as well as challenge the dominant social stereotypes that misconstrue disability as inability. Utilising a qualitative research design, semi-structured interviews were conducted with five elite para-athletes from various sporting backgrounds and analysed from a psychosocial perspective according to the procedures of theoretical thematic analysis. To invoke greater emotional tone and depth, participant-created visual data were used to supplement the initial thematic analysis. Three themes associated with the implicit beliefs of para-athletes were identified and termed, (1) on being disabled, (2) achieving is believing and (3) accepting differences or being indifferent. These themes illustrated how participants had to accept the `fixed` nature of their disability first, before they could work towards overcoming its limitations. Through continuously adapting and adjusting their strategies to address setbacks as they occurred, the process of accepting limitations and overcoming setbacks led to increased feelings of self-efficacy and competence, which consequently led to the dominant incremental beliefs participants held.